PROSES INOVASI PELAYANAN BUS RAPID TRANSIT (BRT) TRANS SEMARANG (STUDI KASUS E-TICKETING) - Budipratama, Yogi; Khaerani, Thalita Rifda (Journal of Public Policy and Management Review, 2017)
Innovation is one of the important aspects in improving the quality of public services. As innovations were issued by the government bureau, government expected people would appease with the public services. In order to improve services quality in transportation sectors, the local government of Semarang launched e-ticketing feature in Bus Rapid Transit (BRT) Trans Semarang.Aim of this study are to find out the service innovation process in BRT Trans Semarang, discover supporting and opposing factors in service innovation implementation of BRT Trans Semarang.Materials and data were collected through depth interview with informants and observed. Theory of this study are based on Mulgan’s innovation process theory, which are generating possibilities, incubating and prototyping, replicating and scaling up, analyzing and learning.Supporting and opposing theory of service innovation in public sectors by Albury and Clark. Results of this study showed service innovation processes (generating possibilities, incubating and prototyping, replicating and scaling up, dan analyzing and learning) have been in progress by General Service Departement of BRT Trans Semarang. Supporting factors in e-ticketing service innovation are political push, pressure for economy and improved efficiency, and pressure for improved service quality. In the other hand, there are opposing factors in service innovation of e-ticketing included over-reliance on high performers, availability of technology, cultural or organizational constraints, no rewards or incentives, short-term planning and budget, and culture ofrisk aversion. Suggestion from the author are included necessity in recruitment of IT expert staffs and reduce operator workload, adjunct technology supporting the implementation of service innovation and e-ticketing machines, establishment of a special team that handles the implementation of the innovation, granting staff an award, cooperationwith external parties in funding e-ticketing machines,and disciplining staffs who are still difficult in learning and using the features of e-ticketing machines.